Brincar na educação infantil como experiência de cultura e formação para a vida - Nicolielo, Maria Elisa; Sommerhalder, Aline; Alves, Fernando Donizete (Educação, 2017)
The article is the result of an academic research completed that aimed to know and understand what children teach and learn in social practice to play in early childhood education. The research was participant observation, in the qualitative approach with daily records of course, moments of play free of 14 children with an average age of three years and their teacher in a public early childhood education room. It held a discussion on the qualitative perspective, in light of the theoretical framework, based on three axes of analysis. The results showed that when playing together, children experienced moments of sharing and bargain of toys and play, strengthened bonds of friendship, expressed preferences and ideas, were created strategies to the dynamics of the play, experiencing formation opportunities for life